Numerical Simulation Analysis on Change of Diversion Ratio of North and South Ports in the Lower Reaches of the Minjiang River - XIA Houxing (Renmin Zhujiang)
In order to analyze the change of the diversion ratio of north and south ports in the lower reaches of the Minjiang River and the influence of river channel evolution on this ratio,based on previous research,as well as measured data,this paper studies diversion-ratio change through mathematical models.According to the results,from 1997 to 2020,the diversion ratio of the north and south ports of the Minjiang River changed significantly,with the change before 2009 being greater than that after 2009.From 1997 to 2020,the change of riverbed erosion and siltation was the main factor influencing the change of the diversion ratio of the north and south ports.This results in a decrease of 9.1%~10.6% in the diversion ratio of the north port in the event of a flood once in 50~200 years.Moreover,the narrowing of the river plane also impacted the diversion ratio of the north and south ports to a certain extent,with an impact range of about 3%.The research results can provide technical references for improvement and protection management of the north and south ports in the lower reaches of the Minjiang River,as well as river-related development and construction.